Laughing at death rituals: performances of (in)sincerity in American situation comedies - Salo, Enni; Hakola, Outi; Kyyrö Jere (Informa UK Limited, 2026)
This article analyses depictions of death in popular American sitcoms utilising concepts from performance theory. The chosen shows were How I Met Your Mother, Modern Family, New Girl, and Brooklyn Nine-Nine. Sitcoms’ death situations imitate and comment on the ideals and norms of real-life social performances. Through content analysis and close reading, we found that storylines about death emphasise comedy and social connection within death rituals. Rituals often include humorous mishaps, as the characters defy social expectations. When the deceased is unfamiliar, humor can be grotesque, and characters feel social pressure to perform the role of a grieving person – often unsuccessfully. Rituals also offer a genuine chance for mourning and social support when a loved one passes. Mortality serves as a contrast that highlights the life-affirming message of the shows and the value of long-lasting social bonds. Sitcoms navigate the balance between culturally ideal sincere moments, failing to live up to these ideals, and joking in a light-hearted or even brutal manner. The shows therefore offer the viewers a chance to face death from a safe distance, allowing space for laughter.